2022
DOI: 10.2147/dddt.s336242
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 in Spinal Cord and DRG with AMD3100 Attenuates Colon-Bladder Cross-Organ Sensitization

Abstract: Background: Cross-sensitization of pelvic organs is one theory for why symptoms of gut sickness and interstitial cystitis/bladder pain syndrome overlap. Experimental colitis has been shown to trigger bladder hyperactivity and hyperalgesia in rats. The chemokine receptor CXCR4 plays a key role in bladder function and central sensitization. We aim to study the role of CXCR4 and its inhibitor AMD3100 in colon-bladder cross-organ sensitization. Methods: The colitis model was established by rectal infusion of trini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Other investigations have implicated MIF in mediating inflammatory and neuropathic pain [19], and a spinal site of action has been identified [20,30]. In addition, a recent study reported that spinal CXCR4 receptors mediate colon inflammation-induced bladder hyperalgesia in rats [32]. Thus, taken together, previous evidence and our current results suggest that spinal MIF and its receptors play a role in modulating spinal mechanisms mediating pain, particularly persistent bladder pain.…”
Section: Discussionsupporting
confidence: 81%
“…Other investigations have implicated MIF in mediating inflammatory and neuropathic pain [19], and a spinal site of action has been identified [20,30]. In addition, a recent study reported that spinal CXCR4 receptors mediate colon inflammation-induced bladder hyperalgesia in rats [32]. Thus, taken together, previous evidence and our current results suggest that spinal MIF and its receptors play a role in modulating spinal mechanisms mediating pain, particularly persistent bladder pain.…”
Section: Discussionsupporting
confidence: 81%
“…The convergent neurons in the DRG have dichotomous afferents; the cell bodies of sensory nerve fibers from two different organs are present in the same DRG. Therefore, it can be activated due to inflammation in one organ to produce these substances and transfer them to another organ, promoting the occurrence and development of neurogenic inflammation of cross-activation between organs [ 23 24 ]. In addition, sensory nerves play an essential role in the generation and development of pain.…”
Section: Autonomic Nervous System Regulation Of Inflammation Pain And...mentioning
confidence: 99%
“…Additionally, the central centers that direct sympathetic and parasympathetic nerves influence organ functions if activated and sensitive. It is how prostatitis could affect the cardiovascular system, ejaculatory function, skin reactions, and bladder activity [ 23 24 72 ].…”
Section: Autonomic Nervous System Dysfunction’s Close Relation With C...mentioning
confidence: 99%